National Athletic Trainers' Association position statement: skin diseases - Zinder, S. M.; Basler, R. S. W.; Foley, J.; Scarlata, C.; Vasily, D. B. (Journal of Athletic Training, 2010)
Objective: To present recommendations for the prevention, education, and management of skin infections in athletes. Background: Trauma, environmental factors, and infectious agents act together to continually attack the integrity of the skin. Close quarters combined with general poor hygiene practices make athletes particularly vulnerable to contracting skin diseases. An understanding of basic prophylactic measures, clinical features, and swift management of common skin diseases is essential for certified athletic trainers to aid in preventing the spread of infectious agents. Recommendations: These guidelines are intended to provide relevant information on skin infections and to give specific recommendations for certified athletic trainers and others participating in athletic health care.